Microwave-Assisted Synthesis of Tin Dioxide Nanocrystals on the Surface of Polypropylene Melt-Blown Nonwovens; Advanced Materials Research : Advanced materials, synthesis, development and application; Vol. 880 : Prospects of Fundamental Sciences Development (PFSD-2013) - Lysak I. A. Ilya Aleksandrovich; Lysak G. V.; Malinovskaya T. D.; Sachkov V. I. (2014, 2014)
Title screen